ANALISIS PEMIKIRAN PROF ALI YAFIE TERHADAP PENGELOLAAN EKOLOGI BERKELANJUTAN MELALUI PRINSIP HIFZ AL BĪʻAH - Faizal; Abd Rahman R; Zaenal Abidin (TAHKIM, 2025)
This article aims to analyse Prof. Ali Yafie's thoughts on hifz al-bī'ah (environmental preservation) in the context of Maqāṣid al-Syarīʻah and its implications for sustainable ecological management. This study employs a literature review method, involving the collection and analysis of various relevant sources, such as books, scientific articles, and documents related to Prof. Ali Yafie's thoughts and the principles of hifz al-bī’ah in Islam. The results of the study show that Prof. Ali Yafie views environmental conservation as part of humanity's responsibility as khalīfah on earth, which is not only related to moral aspects but also to Islamic religious teachings. His thoughts integrate hifz al-bī’ah as part of Maqāṣid al-Syarīʻah, which focuses on five main objectives, namely religion (dīn), soul (nāfs), intellect (‘aql), offspring (nāsl), and wealth (māl), with the addition of the environment as a component that must be protected. In the discussion, this article also reveals practical solutions offered by Prof. Ali Yafie to address ecological challenges such as climate change, deforestation, and pollution, involving a paradigm shift in development, ecological awareness, and active community participation. The implications of this thinking are highly relevant in developing sustainable development policies, particularly in developing countries like Indonesia, by integrating Islamic values into natural resource management and environmental conservation. Keywords: hifz al-bī’ah, maqāṣid al-syarīʻah, environmental conservation, sustainable ecological management